Arsakiden und andere parthische Fürsten als Anhänger fremder Religionen - Metzler, Dieter (Anabasis. Studia Classica et Orientalia, 2010)
The paper deals with several personalities of the Arsakid and post-Arsakid periods known as representing or supporting different religions, including Mani, Abgars in Edessa (followers of Christianity), Gregory the Illuminator in Armenia (called the Apostle of Armenia), Izates in Adiabene (a convert to Judaism), An Shigao (a Buddhist missionary in China), and Vologaises (a mysterious priest in Thracia).